The relationship of CASP 8 polymorphism and cancer susceptibility: a meta-analysis - Ji, G. H.; Li, M.; Cui, Y.; Wang, J. F. (Cellular and Molecular Biology, 2014)
Caspase-8 (CASP8), member of the caspase cysteine protease family, plays an important role in cancer development. CASP8 D302H (rs1045485) (D, Aspartate; H, Histidine) and CASP8 -652 6N del (rs3834129) polymorphisms have been reported to be associated with Cancer susceptibility. However, there are many controversies on this issue. Therefore we performed this meta-analysis with 32 publications, which include 25800 case and 31964 control subjects for CASP8 -652 6N del polymorphism, and 36883 cases and 41089 controls for D302H polymorphism. The results demonstrated that the -652 6N del frequency showed significant difference between case and control group (del versus ins: OR=0.92; 95% CI: 0.90–0.95, p<0.00001). Homozygous, dominant and recessive genotypes were significantly associated with cancer risks. For D302H polymorphism, data indicated the association of allele C with decreased cancer risk (Overall, C versus G: OR=0.93; 95% CI: 0.86–0.99, p=0.03). All genetic models also indicated the significant association with cancer risk especially in Asian population. Further subgroup analysis indicated that CASP8 -652 6N del polymorphism was associated with breast cancer, lung and gastrointestinal cancer susceptibility. CASP8 D302H was found to be only associated with breast cancer risk. Therefore, these two CASP8 variations could be regarded as potential biomarkers for cancer risk.